Presentation of COVID-19 symptoms in acute and post-acute phases in elite athletes: Systematic review - Pasya, M. S. N.; Perdana, S. S.; Azizah, A. N. (Proceedings of the International Conference on Health and Well-Being (ICHWB 2022), 2023)
Infection with the COVID-19 Virus affects the health level of athletes. There is still a lack of data regarding to the prevalence of COVID-19 in athletes, so other supporting information is required to predict an impact on their health. This study aimed to report the acute and post-acute presentation of COVID-19 in athletes. This systematic review research was obtained through four databases namely Google Scholar, PUBMED, SCOPUS, and SPORTDiscus. Assessment of article quality conducted with The Joanna Briggs Institute (JBI) Critical Appraisal. Then, nine articles were obtained whose research population was elite athletes. Six articles represented acute infection of COVID-19 and three other articles described post-acute infection of COVID-19 in elite athletes. The data of this study from the presentation of COVID-19 in athletes showed that it does not cause symptoms until the symptoms were mild. Meanwhile, in post-acute COVID-19, in most athletes, persistent symptoms can negatively impact their performance, which affects their recovery time.